The Influence of Habib Jafar's Personal Branding on Social Media (Instagram) on Social Religious Behavior - Hopipah, Nur; Muary, Rholand (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
Social media, particularly Instagram, facilitates global social interaction and allows users to share stories and build self-images, known as personal branding. This study examines how Habib Jafar, a religious influencer, uses personal branding on Instagram to influence his followers' religious social behavior. The research aims to analyze the impact of Habib Jafar's personal branding on his followers' religious social behavior. Using a quantitative approach, 100 Instagram followers of Habib Jafar were surveyed with a 41-question questionnaire on a 1-5 scale. The data were analyzed using normality, linearity, and regression tests with SPSS 22. The findings show that the data distribution is normal and linear, and the regression test indicates a significant influence of personal branding on religious social behavior, with a significance value of 0.000 0.05.